Clinical Improvement of Patients With Complications of Exfoliativa Dermatitis: A Case Report - Christabella, Nathania; Primas Adjie, Sugih; Rusetiyanti, Nurwestu; Anggorowati, Nungki; Raisa, Husna (Jurnal Health Sains, 2024)
Exfoliative dermatitis or erythroderma is a severe skin inflammatory syndrome, characterized by erythema and desquamation more than 90% of the body surface area. Previous study shown erythroderma incidence was 83 people in 2011 to 2014. Incidence of erythroderma in Portugal 9.4 cases per year, with the predominance age of 41 to 61 years. The most common etiology of erythroderma is psoriasis and dermatitis. A woman Mrs. T, 55 years old, came to emergency room Rajawali Citra General Hospital Bantul on 5 September 2023 with complaints of abdominal pain, frequent vomit, cough and itchy and dry skin on the face, upper limbs and lower limbs. Patient has erythroderma medical history since a year ago. On dermatological examination, the facial showed patch erythema with scales on left suprasilia and nasales, the upper and lower limbs showed xerotic. This patient was diagnosed with erythroderma with improvements. Patient was treated with Loratadine 10 mg tablets once a day orally and Desoximethasone oint twice a day. Erythroderma treatment depends on its underlying disease. The main therapy is using petrolatum, emollient or low-potency topical steroid to maintaince skin barrier function and reduce inflammatory. Antihistamines can be used to relieve pruritus and as antianxiety agent. A well combination drugs therapy shows clinical improvement on erythroderma performance.